(untitled) - RUDI KASENDA, SAIKO (Language Horizon: Journal of Language Studies, 2014)
AN ANALYSIS OF SPEECH ACTS IN MARTIN LUTHER KING’S “I HAVE A DREAM” SPEECH Saiko Rudi Kasenda English Literature, Faculty of Languages and Arts, Surabaya State University rudisaikokasenda@gmail.com Lisetyo Ariyanti, S.S., M.Pd. English Department, Faculty of Languages and Arts, Surabaya State University lisetyo.a@yahoo.com ABSTRAK Memerintah seseorang telah menjadi sesuatu yang amat umum di masyarakat. Hal tersebut selalu terjadi di setiap aspek ketika berkomunikasi yang tanpa disadari terjadi. Ini dapat didefinisikan sebagai speech act yang pada dasarnya adalah suatu tindakan yang dilakukan melalui perkataan. Fokus skripsi ini adalah speech act yang diucapkan Martin Luther King di pidatonya yang berjudul “I Have a Dream”. Rumusan masalah yang diajukan pada skripsi ini adalah (1) Apakah makna yang tersirat dari speech acts yang diucapkan Martin Luther King di pidatonya yang berjudul “I Have a Dream”?, (2) Bagaimana speech acts yang diucapkan Martin dapat mempengaruhi pendengarnya?, dan (3) Apakah yang diharapkan Martin melalui speech acts yang diucapkan pada pidatonya tersebut? Skripsi ini bertujuan untuk mengungkap speech acts yang diucapkan oleh Martin Luther King. Dalam hal ini, skrispsi ini mencoba menganalisa makna tersirat yang terdapat dalam speech acts yang diucapkan oleh Martin Luther King, bagaimana speech acts tersebut dapat mempengaruhi pendengarnya, serta tindakan yang diharapkan oleh Martin dalam speech acts-nya. Metode deskriptif kualitatif beserta teori dari Yule dan Searle diaplikasikan di dalam skripsi ini. Ada beberapa langkah yang diterapkan dalam skripsi ini. Langkah-langkah tersebut adalah menganalisa makna tersirat dari speech acts yang diucapkan oleh Martin beserta tipe locutionary dan illocutionary-nya, menganalasi pengulangan sebagai cara bagi Martin untuk mempengaruhi pendengarnya, dan menganalisa tindakan yang diharapkan Martin dari speech acts-nya. Hasil dalam skripsi ini menunjukkan bahwa speech acts Martin memiliki berbagai makna tersirat. Hal ini merupakan pencerminan dari cara Martin mencoba mempengaruhi pendengarnya mengenai hal yang berkaitan dengan diskriminasi dan ketidakadilan yang terjadi pada orang kulit hitam pada saat itu. Pengulangan yang terdapat pada pidato “I Have a Dream” juga dapat dipahami sebagai caranya untuk mempengaruhi pendengarnya dan juga pandangannya sebagai figur yang sangat berpengaruh di masa Civil Rights Movement. Speech acts yang diucapkan Martin juga dapat dilihat sebagai caranya untuk menunjukkan harapan dan aspirasinya. Ini disebabkan karena speech acts-nya adalah wadah bagi Martin untuk menentang ketidakadilan pada orang kulit hitam. Dalam hal ini, pengulangan pada speech acts menunjukkan bahwa harapan yang dimiliki Martin sangatlah kuat. Penggunaan kekuasaan juga dapat dipahami dari speech acts Martin. Kata kunci: speech act, locutionary act, illocutionary act, perlocutionary act ABSTRACT Getting other people to do something has been something very common in our society. It is something that always occurs in human interaction in almost every aspect in our lives which is unconsciously done. This is defined as speech act which is basically described as type of action performed by a speaker with the utterance (Yule, 2006, p. 118). This study focuses on speech act performed by Martin Luther King Jr in his speech called “I Have a Dream”. The research questions proposed in this study are (1) What are intended meanings in Martin Luther King’s speech acts in his “I Have a Dream” speech?, (2) How do Martin’s speech acts in his “I Have a Dream” speech engage the audience?, and (3) What are actions hoped by Martin Luther King in his speech acts?.The purpose of this study is to reveal the significance of speech acts performed by Martin Luther King. This study includes the analysis of intended meanings embedded in Martin’s speech acts, how the speech acts are able to engage the audience as well as actions hoped by Martin in his speech acts. The writer applies descriptive and qualitative method and speech act theory from Yule and Searle. In the data analysis, there are several steps which are applied, they are analyzing intended meanings in Martin’s speech acts as well as its locutionary act and illocutionary act type, analyzing repetition as the mean that allows Martin to engage the audience, and analyzing hope that is implied in his speech acts. The result shows that Martin’s speech acts have various intended meanings. This is as the result of how Martin tried to engage the audience about matters related to discrimination and injustices towards the African-Americans or the Negro people. In this case, repetition that appears in many of Martin’s speech acts is seen as the signal of his attempt to influence the audience as well as his vision as the widely influential figure who fought for justice for the Negro people during the Civil Rights Movement. As Martin’s speech acts in his “I Have a Dream” are the form of his strong resistance of the discrimination and injustices, they also serve as the mean to show his hope or aspiration as well. In this case, repetitions in his speech acts are seen as the signal that Martin’s hopes are strongly spoken. The use of power is also revealed in Martin’s speech acts. Key words: speech act, locutionary act, illocutionary act, perlocutionary act INTRODUCTION When someone says something such as “I’m so thirsty” to his boyfriend, then the boy would immediately do something. He would bring a glass of fresh water to the girlfriend so that she would not be thirsty anymore. This indicates how the girlfriend as the speaker can make someone else to do something without deliberately asking the person by saying “Could you please bring me a glass of water?” or “Fetch me a glass of water, please.” This is the case of how speech act occurs. It is basically defined as the actions performed in saying something (Cutting, 2002, p. 16). It can be understood through different levels and through various approaches. In this case, a speech can be understood through Speech Act Theory which is a part of Pragmatics. Speech act theory is related to description of actions such as ‘requesting’, ‘commanding’, ‘questioning’, or ‘informing’ (Yule 2006: 118). Speech acts are classified into three levels; locutionary acts, illocutionary acts, and perlocutionary acts (Cutting, 2002, p.16). It will be interesting to analyze public speech spoken by someone more deeply through its speech acts since it is found that people or hearers are not actually aware about the intended meanings that a speaker has delivered. A public speech called “I Have a Dream” by Martin Luther King Jr. is chosen as the data source of the study since it contains intended meanings and associations to social phenomena that captured the portrayal of inequality, power abuse, and the use of power. Speech Acts is not something new to be analyzed. It has been analyzed by Murmaniati, Riyanto and Christy as main points of their study. Murmaniati used a book containing Soekarno’s public speech as the data to analyze his speech acts. The speech is used by Soekarno as a way to protest about injustice done by the government of Netherland at that time. While Murmaniati used Soekarno’s speech as her source of data, Riyanto used a literary work called ‘Fences’ written by Pulitzer Prize winner August Wilson. ‘Fences’ is a drama about black people in 1950s. He analyzed the speech acts used by characters to show how the characters in the drama could engage other characters to do something. The speech act is also employed by Christy to be analyzed in her research study. She used a literary work as her source of data as well. She used George Bernard Shaw’s novel called ‘Arms and the Man’ to show how speech acts could raise the issue of power. This study will try to analyze speech acts spoken by Martin Luther King Jr in his “I Have a Dream” speech by applying speech act theory which is a part of pragmatics. Historical values contributing to the production of Martin Luther King Jr’s speech acts such as social aspects and culture at that time will be the points that would lead to answering the conducted research questions. The research questions of this study are: (1) What are intended meanings in Martin Luther King’s speech acts in his “I Have a Dream” speech mean?, (2) How do Martin Luther King’s speech acts in his “I Have a Dream” speech engage the listeners?, and (3) What are actions hoped by Martin Luther King from his speech acts? This study is conducted to find the intended meanings in speech acts spoken by Martin Luther King in his “I Have a Dream” speech, to find out how speech acts in Martin Luther King’s “I Have a Dream” speech engage the listeners, and to find out the actions hoped by Martin Luther King from his speech acts in his “I Have a Dream” speech. The significance of the study is to make the readers understand the significance of the use of speech acts used in Martin Luther King ’s “I Have a Dream” speech. Moreover, it is hoped that this study could be a reminder of the importance of appreciating other people’s right without looking at their race and social status. Several theories are applied in conducting this study. The first theory is speech act theory comes byYule and Searle. In very general terms speech acts are the type of action performed by a speaker with the utterance (Yule, 2006, p. 118). Another theory used in this study is from Hymes and Brown. In this case, the theory is referring to context that determine, specify, or clarify the meaning of an event or other occurrence. Repetition theory from Tannen and Murmaniati are also applied in this study. Another theory used in this study is by Fairclough and Foucault which refers to power in discourse. RESEARCH METHOD Descriptive qualitative is the method used in this study. Descriptive qualitative method is concerned with structures and patterns. Since this study focuses on Martin Luther King’s speech acts, the subject of this study is Martin himself. He was the writer and the sole speaker of the speech. The source of data used in this study is taken from Martin Luther King Jr’s “I Have a Dream” speech. The researcher uses utterances in Martin Luther King Jr’s speech called “I Have a Dream” as the source of the data. Meanwhile, the data used in this study is utterances from Martin Luther King Jr’s “I Have a Dream” speech. Observation is applied as the mean to find out the answers of the the research questions. In this study, the writer and “I Have a Dream” by Martin Luther King Jr. are the instruments who observes Martin Luther King’s “I Have a Dream” speech. The writer uses his skill to collect the data from various sources. The point in which the writer is the primary instrument or medium through which the research is conducted (Lofland, Snow, Anderson, & Lofland, 2006, p. 3), Laptop/computer, digital files and other electronic devices are used as the tools to support the instruments and data in conducting this study. In conducting data analysis in his research study the researcher uses some procedures and techniques. There are three steps of analyzing data: data reduction, data display, conclusion, and verification (Miles and Huberman, 1992, p. 20). In order to answer the three research questions, understanding features of context is the first step that will be done. The researcher will focus on matters related to the “I Have a Dream” speech such as the addressor of the speech, the addressee in locutionary and illocutionary speech acts. The Analysis of the study are based on the three research questions: The first research question is about intended meanings in Martin Luther King’s speech acts. The first step of answering the first research question is Answering Features of Context, such as participant, topic, setting, channel, code, event, key, and purpose are the first thing that will be done. Then, it will be followed by classifying Locutionary Act. In this stage utterances are classified into several locutionary acts (Declarative Imperative, or Interrogative). After that, the intended meanings are analyzed by reviewing the context and the locutionary act. After finding out the intended meanings in speech acts spoken by Martin Luther King Jr, Searle’s theory and other theories are used to classify illocutionary speech act. Based on his theory, there are five categories of illocutionary speech act (representative, directive, comissive, expressive, and declaration). The second research question is about how Martin’s speech acts are able to engage the audience. In this case, the question is answered by using repetition theory by Murmaniati and Tannen. The repetitions in Martin’s speech acts are analyzed to find out its functions that can contribute to the speech acts. The third reserach question is about hopes implied in Martin’s speech acts. The hopes are the representation of the perlocutionary acts. In order to answer the question, the first thing that will be done is reviewing the intended meanings embedded in the speech acts produced by Martin Luther King Jr and how the repetition of his speech acts employed by Martin could engage his audience. DATA ANALYSIS AND DISCUSSION Data Analysis On this section, the analysis of the first, the second, and the third research questions are shown each data. Each data consists of Martin’s speech acts followed by the analysis which are presented by using three paragraphs. The first section displays the analysis the first research question. The second section displays the analysis the second research question. And the third section displays the analysis of the third research question. Presentation of Data 2 Intended Meanings in Martin’s Speech Acts in Data 2 Two speech acts in the passage above contain Martin Luther King Jr’s intended meanings, how they can engage the audience, and hope beneath them. Martin’s refusal toward the notion of the absence of opportunity to achieve justice is the theme of the speech acts above. The speech acts above can be seen on paragraph 5 in line 39 to line 43. It is understood that Martin Luther King Jr’s put himself as the symbol of himself and his audience who cannot accept injustice toward Negro people. In this case, Martin uses the phrase “the bank of justice” and “insufficient funds” in the speech acts to reflect Martin’s denial towards the state where they do not have a chance to achieve racial justice. In this case, the speech act has intended meaning of refusal. It demonstrates Martin’s disbelief that there is nothing that can be done to get racial justice and to end segregation and discrimination towards the Negro people. The speech act above also seems to have another intended meaning. It is not just about Martin Luther King Jr’s refusal of injustice which is racism toward Negro people. It is also understood that the speech act has an intended meaning of suggesting. The speech act above proposes the audience to have the same belief that there is still opportunity to fight for racial justice. It shows that Martin would like to influence the audience that somehow racial justice can be achieved as long as they believe that it can be accomplished. The speech acts above can be categorized as comissive speech act which is a representation of Martin Luther King Jr’s rejection toward racism of Negro people. As a speech act that has intended meaning of suggestion, which is to have the audience the same belief that racial justice can be achieved, it can be classified as directive speech act which commits other people to do something. How Speech Acts in Data 2 Engage the Audience How Martin Luther King Jr could engage his audience is associated in the use of repetition of words “we refuse to believe” in his speech acts above. It can be known that the words “we refuse to believe” are repeated twice. As can be noticed on the speech acts above, the words “we refuse to believe” is followed by clauses such as “there are insufficient funds in the great vaults of opportunity of this nation” and “the bank of justice is bankrupt.” Those can be understood as the reflections of racism of Negro people. The existence of repetition in those speech acts is understood to emphasize particular circumstances. It is reflected by how the indications of strong resistance of Martin Luther King Jr toward racial injustice of Negro people are easily recognized in those speech acts. It implies Martin Luther King Jr’s will to ask his audience to reject whatever segregation that happened to Negro people and to gain righteousness that had been fought for so long. It is understood that Martin Luther King Jr would like to prove his audience that there was still an opportunity that could be achieved to end racism of Negro people. The use of repetition can also be understood to give the audience a thought that racial injustice could be ended them if they have courage to make a change. Hope Implied in Martin’s Speech Acts in Data 2 The speech acts above express what Martin Luther King Jr felt delivered through locutionary act of declarative. In this case, the speech acts have intended meanings of suggesting and refusing. The speech acts are intended to offer Martin Luther King Jr’s audience an idea to do the same thing like Martin Luther king Jr did which was rejecting racism toward Negro people. They also have an intended meaning of refusal which put Martin Luther King Jr and his audience to have no tolerance to injustice toward Negro people. Those speech acts can be classified as comissive act which express Martin Luther King Jr’s refusal. It can also be interpreted as directive speech acts having intended meaning of suggesting.. The use of repetition “we refuse to believe” reflects how the strong resistance of Martin Luther King Jr toward racial injustice of Negro people is easily recognized in those speech acts. It is understood that Martin Luther King Jr would like to prove his audience that there was still an opportunity that could be achieved to end racism of Negro people. By looking at those speech acts explained before, it can be seen that Martin Luther King Jr hoped that he wanted the audience to have the same point of view that justice can achieved as long they believe that it can be accomplished. It can also be understood that Martin would like to influence the audience to refuse that there is no chance left for them to gain justice and to end racial discrimination. The realization of Martin’s hope in the speech acts above is the signing of Civil Rights Act of 1964, Voting Rights of Act of 1965, and Civil Rights Act of 1968. Those acts are signed to end segregation and discrimination of the African-American people and to open opportunity for them to live and to vote. SUMMARY OF DATA ANALYSIS Summary of Intended Meanings in Martin Luther King’s Speech Acts Martin’s speech acts are found to have various intended meanings. They are spoken by him as statement of fact, as complaint, as refusal, as suggestion, as persuasion, and as assertion. Table 1: Intended Meanings in Martin’s Speech Acts Data Speech Act Locutionary Type Illocutionary Type Intended Meaning 1 One hundred years later, we must face the tragic fact that the Negro is still not free. Statement Expressive & Representative As statement of fact and as a complaint. 1 One hundred years later, the life of the Negro is still sadly crippled by the manacles of segregation and the chains of discrimination. Statement Expressive & Representative As statement of fact and as a complaint. 1 One hundred years later, the Negro lives on a lonely island of poverty in the midst of a vast ocean of material prosperity. Statement Expressive & Representative As statement of fact and as a complaint. 1 One hundred years later, the Negro is still languishing in the corners of American society and finds himself an exile in his own land. Statement Expressive & Representative As statement of fact and as a complaint. 2 We refuse to believe that the bank of justice is bankrupt. Statement Comissive & Directive As a refusal and as a suggestion 2 We refuse to believe that there insufficient funds in the great vaults of opportunity of this nation. Statement Comissive & Directive As a refusal and as a suggestion 3 Now is the time to rise from the dark and desolate valley of segregation to the sunlit path of racial justice. Statement Directive As a suggestion 3 Now is the time to open the doors of opportunity to all of God's children. Statement Directive As a suggestion 3 Now is the time to lift our nation from the quicksands of racial injustice to the solid rock of brotherhood. Statement Directive As a suggestion 4 We must forever conduct our struggle on the high plane of dignity and discipline. Statement Directive As a suggestion 4 We must not allow our creative protest to degenerate into physical violence. Statement Directive As a suggestion 5 We can never be satisfied as long as our bodies, heavy with the fatigue of travel, cannot gain lodging in the motels of the highways and the hotels of the cities. Statement Expressive As a complaint 5 We cannot be satisfied as long as the Negro's basic mobility is from a smaller ghetto to a larger one. Statement Expressive As a complaint 5 We can never be satisfied as long as a Negro in Mississippi cannot vote and a Negro in New York believes he has nothing for which to vote. Statement Expressive As a complaint 6 Go back to Mississippi, go back to Alabama, go back to Georgia, go back to Louisiana, go back to the slums and ghettos of our northern cities, knowing that somehow this situation can and will be changed. Statement Directive As a suggestion 7 “I have a dream that one day this nation will rise up and live out the true meaning of its creed: "We hold these truths to be self-evident: that all men are created equal." Statement Representative As a persuasion 7 “I have a dream that one day on the red hills of Georgia the sons of former slaves and the sons of former slave owners will be able to sit down together at a table of brotherhood.” Statement Representative As a persuasion 7 “I have a dream that one day even the state of Mississippi, a desert state, sweltering with the heat of injustice and oppression, will be transformed into an oasis of freedom and justice.” Statement Representative As a persuasion 7 “I have a dream that my four children will one day live in a nation where they will not be judged by the color of their skin but by the content of their character.” Statement Representative As a persuasion 8 With this faith we will be able to hew out of the mountain of despair a stone of hope. Statement Representative & Directive As an assertion and as a suggestion. 8 With this faith we will be able to transform the jangling discords of our nation into a beautiful symphony of brotherhood. Statement Representative & Directive As an assertion and as a suggestion. 8 With this faith we will be able to work together, to pray together, to struggle together, to go to jail together, to stand up for freedom together, knowing that we will be free one day. Statement Representative & Directive As an assertion and as a suggestion. 9 And if America is to be a great nation this must become true. So let freedom ring from the prodigious hilltops of New Hampshire. Statement Directive As a sugestion 9 Let freedom ring from the mighty mountains of New York. Statement Directive As a suggestion 9 Let freedom ring from the heightening Alleghenies of Pennsylvania! Statement Directive As a suggestion 9 Let freedom ring from the snowcapped Rockies of Colorado! Statement Directive As a suggestion 9 Let freedom ring from the curvaceous slopes of California! Statement Directive As a suggestion Summary of How Martin Luther King’s Speech Acts Engage the Audience Repetitions in Martin Luther King’s speech acts play such a significant part in his “I Have a Dream” speech. It is seen as a medium that allows Martin to engage the audience. In this case, the repetitions are found to have various functions, such as: as reminder, as an objection, to show Martin’s dissatisfaction, to show Martin’s assurance, as an advice, and to unite his audience. Table 2: Repetition in Martin Luther King’s Speech Acts Data Speech Acts Repeated Sentence or Phrase Function 1 ““One hundred years later, we must face the tragic fact that the Negro is still not free. One hundred years later, the life of the Negro is still sadly crippled by the manacles of segregation and the chains of discrimination. One hundred years later, the Negro lives on a lonely island of poverty in the midst of a vast ocean of material prosperity. One hundred years later, the Negro is still languishing in the corners of American society and finds himself an exile in his own land.” One hundred years later As a reminder 2 “We refuse to believe that the bank of justice is bankrupt. We refuse to believe that there insufficient funds in the great vaults of opportunity of this nation.” We refuse to believe As an objection 3 “Now is the time to rise from the dark and desolate valley of segregation to the sunlit path of racial justice. Now is the time to open the doors of opportunity to all of God's children. Now is the time to lift our nation from the quicksands of racial injustice to the solid rock of brotherhood.” Now is the time To urge the audience to take actions 4 “We must forever conduct our struggle on the high plane of dignity and discipline. We must not allow our creative protest to degenerate into physical violence.” We must As an advice 5 “We can never be satisfied as long as our bodies, heavy with the fatigue of travel, cannot gain lodging in the motels of the highways and the hotels of the cities. We can never be satisfied as long as the Negro's basic mobility is from a smaller ghetto to a larger one. We can never be satisfied as long as a Negro in Mississippi cannot vote and a Negro in New York believes he has nothing for which to vote.” We can never be satisfied To show Martin’s dissatisfaction 6 “Go back to Mississippi, go back to Alabama, go back to Georgia, go back to Louisiana, go back to the slums and ghettos of our northern cities, knowing that somehow this situation can and will be changed.” Go back to As a reminder 7 “I have a dream that one day this nation will rise up and live out the true meaning of its creed: "We hold these truths to be self-evident: that all men are created equal." “I have a dream that one day on the red hills of Georgia the sons of former slaves and the sons of former slave owners will be able to sit down together at a table of brotherhood.” “I have a dream that one day even the state of Mississippi, a desert state, sweltering with the heat of injustice and oppression, will be transformed into an oasis of freedom and justice.” “I have a dream that my four children will one day live in a nation where they will not be judged by the color of their skin but by the content of their character.” I have a dream. To show Martin’s aspiration 8 “With this faith we will be able to hew out of the mountain of despair a stone of hope. With this faith we will be able to transform the jangling discords of our nation into a beautiful symphony of brotherhood. With this faith we will be able to work together, to pray together, to struggle together, to go to jail together, to stand up for freedom together, knowing that we will be free one day.” With this faith To show Martin’s assurance 9 And if America is to be a great nation this must become true. So let freedom ring from the prodigious hilltops of New Hampshire. Let freedom ring from the mighty mountains of New York. Let freedom ring from the heightening Alleghenies of Pennsylvania! Let freedom ring from the snowcapped Rockies of Colorado! Let freedom ring from the curvaceous slopes of California! Let freedom ring To unite his audience Summary of Hopes Implied in Martin Luther King’s Speech Acts The following is a table containing the simplification of what has been conducted on the analysis section. The table contains Martin’s speech acts and hope implied beneath them. Table 3: Hopes Implied in Martin’s Speech Acts Data Speech Act Speech Act Type Hopes (Perlocutionary Act) 1 “One hundred years later, we must face the tragic fact that the Negro is still not free. One hundred years later, the life of the Negro is still sadly crippled by the manacles of segregation and the chains of discrimination. One hundred years later, the Negro lives on a lonely island of poverty in the midst of a vast ocean of material prosperity. One hundred years later, the Negro is still languishing in the corners of American society and finds himself an exile in his own land.” That the audience would be reminded that the Negro people are the victims of racial discrimination for hundreds of years. 2 We refuse to believe that the bank of justice is bankrupt. We refuse to believe that there insufficient funds in the great vaults of opportunity of this nation. That the audience would have the same point of view that justice for the Negro people can be achieved as long as they believe it can be accomplished. 3 Now is the time to rise from the dark and desolate valley of segregation to the sunlit path of racial justice. Now is the time to open the doors of opportunity to all of God's children. Now is the time to lift our nation from the quicksands of racial injustice to the solid rock of brotherhood. That the audience should start to make a change by fighting for racial justice and ending segregation. That the Negro people have the same opportunity as white people have. 4 “We must forever conduct our struggle on the high plane of dignity and discipline. We must not allow our creative protest to degenerate into physical violence.” That Martin’s supporters would never use violence in protesting for justice of the Negro people. 5 “We can never be satisfied as long as our bodies, heavy with the fatigue of travel, cannot gain lodging in the motels of the highways and the hotels of the cities. We cannot be satisfied as long as the Negro's basic mobility is from a smaller ghetto to a larger one. We can never be satisfied as long as a Negro in Mississippi cannot vote and a Negro in New York believes he has nothing for which to vote.” That the unfairness that the Negro people suffered must be ended in a way that they should gain the right to rest at a motel or any other facilities 6 “Go back to Mississippi, go back to Alabama, go back to Georgia, go back to Louisiana, go back to the slums and ghettos of our northern cities, knowing that somehow this situation can and will be changed.” That the audience would have the conviction that situations in parts of The United States can be changed to the better one. 7 “I have a dream that one day this nation will rise up and live out the true meaning of its creed: "We hold these truths to be self-evident: that all men are created equal." “I have a dream that one day on the red hills of Georgia the sons of former slaves and the sons of former slave owners will be able to sit down together at a table of brotherhood.” “I have a dream that one day even the state of Mississippi, a desert state, sweltering with the heat of injustice and oppression, will be transformed into an oasis of freedom and justice.” “I have a dream that my four children will one day live in a nation where they will not be judged by the color of their skin but by the content of their character.” That the racist people would realize that all human beings, including the Negro, are just the same. That the States in America, heavily plagued with racial discrimination, would turn out to be the place would respect the Negro people without looking at their racial identity. 8 “With this faith we will be able to hew out of the mountain of despair a stone of hope. With this faith we will be able to transform the jangling discords of our nation into a beautiful symphony of brotherhood. With this faith we will be able to work together, to pray together, to struggle together, to go to jail together, to stand up for freedom together, knowing that we will be free one day.” That the audience would have the belief that somehow racial injustice and discrimination can be ended. 9 And if America is to be a great nation this must become true. So let freedom ring from the prodigious hilltops of New Hampshire. Let freedom ring from the mighty mountains of New York. Let freedom ring from the heightening Alleghenies of Pennsylvania! Let freedom ring from the snowcapped Rockies of Colorado! Let freedom ring from the curvaceous slopes of California! That freedom for the Negro people must be unleashed immediately in states in America such as New Hampshire, New York, Pennsylvania, Colorado, and California DISCUSSION In the discussion section, the elaboration of the entire analysis that has been conducted is explained to present the final result. The discussion section consists of the elaboration of the intended meaning of Martin Luther King’s speech acts, how the speech acts could engage the audience, and the Martin’s hope embedded in the speech acts which will be discussed with the theories that have been applied and with the previous studies which are used in this study. Discussion of Intended Meanings in Martin Luther King’s Speech Acts The intended meanings that have been found are connected with how the speech acts serve as Martin’s expression and his intention to persuade his audience to commit for future actions and other related matters. It is found that Martin’s speech acts in his “I Have a Dream” speech are intended as statement of fact, as complaint, as refusal, as suggestion, as persuasion, and as assertion. One of the intended meanings in Martin’s speech acts that can be seen is to state a fact consisting description of an event or a situation. It is how Martin, the sole speaker of the speech, was able to tell the truth of what happened as well as the history that drove the event of “I Have a Dream” to occur in August 28, 1963. This can be seen in speech acts in Data 1. In this case, it can be confirmed that Martin Luther King Jr has fulfilled the requirement of speech act, which is representative act, that drives him to confront his audience with the truth or fact regarding to racial injustice of the Negro people. Representative act is speech act whose purpose is to commit the speaker to something’s being the case, to the truth of the expressed position (Searle, 1975). This view is also supported by Yule that said the speech act can has the ability to state what the speaker believes to be the case (Yule, 1996, p. 53). In other words, Martin’s speech act has the capacity to make his audience to have thoughts of what really happened to the Negro people as the outcome of racial injustice and discrimination. As a speech act that has an intended meaning to commit people to do a particular action, Martin Luther King’s speech act supports the landmark of speech acts that says it is an action done via utterance. It has the ability to make other people to do something. In this case, the speech act has a tendency to persuade people who supported Martin to not do any harm as a part of their protest towards racial injustice and discrimination of the Negro people. The speech act can be perceived as the expression of what Martin Luther King Jr wants (Yule, 1996, p.54). It is found that there are speech acts which have more than one intended meaning. It can be seen in the speech acts in Data 1 and Data 2. Speech acts in Data 1 deals with what happened one hundred years after the Emancipation of Proclamation was approved by the US representatives. While the speech acts in Data 1 have intended meanings to state a fact and to complain, the speech acts in Data 2 have intentions to refuse and to suggest things related to racial discrimination and segregation of the Negro people. In this case, those speech acts reflect with the theory conducted by Searle and Vandeverken. It says that whenever a speaker utters a sentence in an appropriate context with certain intentions, he performs one or more illocutionary acts (Searle & Vandeverken, 1985, p.34). Therefore, it can be concluded that the speech acts in Data 1 and Data 2 fit to the theories that have been described before. Discussion of the Repetitions in Martin Luther King’s Speech Acts Repetition is applied to emphasize certain elements in the mind of the listeners (Murmaniati, 2007, p. 35). According to Tannen, repetition also functions to accomplish social goals and has the ability to bond participants (the addressor and the addressee) linking the speaker in a discourse and in relationships (Tannen, 2007, p. 58-61). The repetition in Martin Luther King Jr’s speech act is used as his mean to engage his audience about matters related to racial injustice and discrimination of the Negro people. In the result section, it is found that repetition is applied in many Martin’s speech acts. The repetition found in the speech acts is words or sentences or phrases or clauses repeated in several different sentences. The words which are repeated in the utterances are seen to have various function, which are as reminder, to show Martin’s aspiration, to unite his audience, as an advice, and as an objection. In this case, it can be said that repetition in Martin’s speech acts is seen to have big contribution towards the meaning of As for the repetitions having function to bond participants, it can be seen that Martin Luther King Jr would like to unite himself with the audience. It is reflected in Martin’s speech acts in Data 3. In this case, the sentence “Now is the time” is repeated three times to unite his audience. The repetition has the ability to unite his audience which eventually is able to urge the audience to take actions regarding to injustices of the Negro people. It can also be noticed in Martin’s speech acts in Data 9. In data 9, it is shown that the repetition of “Let freedom ring” has the function to unite the audience as well. The repetition has the purpose to unite the audience to spread out the notion of freedom and justice of the Negro people to many states in The United States. Since Martin’s speech acts in “I Have a Dream” recount very crucial issues such as racial discrimination and freedom, it can be seen that the theory from Tannen that says repetition has the capacity to accomplish social goals supports the idea of Martin’s speech act itself. It can be understood that how Martin accomplish the social goal, which is to end racial segregation and discrimination, is expressed through the repetitions in many of his speech acts. Discussion of Hopes Implied in Martin LutheKing’s Speech Acts As seen on the table above, it can be seen that Martin hoped that his audiences would be persuaded to act and to have a state of mind regarding to how they should deal with racial discrimination of the Negro people. One of the examples of Martin’s suggestion can be seen on speech acts in Data 5. Martin’s hope speech acts in Data 5 suggest that in order to fight for justice for the Negro people must be done by never using any violence for it would only show that the Negro people are as bad as the racist people who oppose them by doing harm. This shows how Martin’s speech acts can persuade to do a particular thing. This fits with Austin’s belief that the speech act can cause the hearers to feel a requirement to do something (Austin in Horn & Ward, 2004, p.54). Another example that can be seen regarding to how Martin’s hope is embodied in his speech acts can be noticed on Data 1. The speech acts are intended to state the facts that the Negro people have been the victims of racial discrimination for so long. The hope embedded in the speech acts in Data 1 is that the audience would have a state of mind where the Negro people are the victims of racial discrimination for hundreds of years. This also matched with Austin’s theory that the perlocutionary act consist in the production of effects upon the thoughts, feelings, or actions of the addressee in which it can convince the addressee of the truth of a statement (Austin in Horn & Ward, 2004, p. 54). From the explanations delivered above, it is proven that there is hope implied in Martin’s speech acts. The hopes are embedded in Martin’s speech acts which are to state facts or to suggest his audience to do something and so on. This shows that the speech acts do not just have the ability to make the hearers to act, but also it is revealed that speech acts have the capacity to make the hearers to have the urge in doing something. Discussion of Power Used in Martin Luther King’s Speech Acts One of the indications how power is exercised is that Martin Luther King serves as someone who had an influence toward the people who wanted to embrace justice for the Negro people. In this case, Martin is seen as a force that can persuade his audience to deal with injustices of the Negro people. As what Foucault said an agent, which is Martin, has the will to influence other people who to do things which they do not wish to do (Foucault, 2003, p.34). Another circumstance that shows how power is enacted in Martin Luther King’s speech acts is his description of the status quo of the Negro people. It is shown in Martin’s speech acts in Data 1. In the speech acts, the Negro people are told by Martin as the victims of discrimination for hundreds of years. This is considered as a strategy to show how power is exercised. As what Van Dijk said, one strategy of exercising power in discourse is to persuasively define the ethnic status quo as 'natural', lust', 'inevitable' or even as `democratic', for instance through denials of discrimination or racism (Discourse Power and Access, Teun A van Dijk, p.91). It can be concluded that by giving the description of how difficult the Negro people’s lives are can be used as an approach to persuade the audience to face the fact and start to make a change. Since Martin Luther King’s speech acts deal with a matter related to the Negro people as the ones who were discriminated, it can be seen that Martin exercised power in speech acts to allow himself to effect social change. Foucault stated that it opens up the space for individuals to act, to exercise power at the capillaries in order to effect social change. (Power, Discourse, Subjectivity, p.37). It can be said that Martin tried to use his influence as a figure who can persuade his audience to start making a change in terms of ending racial discrimination and justice of the Negro people. This also shows that when power is exercised, it eventually can affect social life. CONCLUSION There are several conclusions that can be drawn regarding to results and discussion that has been conducted. In this case, the conclusions are presented as the outcome of the production of Martin Luther King Jr’s speech acts. One of the conclusions is related to intended meanings in Martin Luther King Jr’s speech acts. In this case, it can be seen that Martin Luther King Jr had used his speech acts to express his thoughts regarding to racial injustice and discrimination of the Negro people. It is found that he delivered his disappointment in many of his speech acts. His disappointment is delivered through how he complained by stating facts which are mostly conveyed by locutionary acts of statement. It proves that although the locutionary acts state facts of what really happened to the Negro people, the speech acts are intended as a form of Martin’s protest towards racial injustice of the Negro people. As for another intended meaning in Martin’s speech act, the speech acts also serve as a way to convey the audience to do a particular action. Just like locutionary acts of statement to complain, this is also done by not deliberately uttering locutionary act of imperative. There is another conclusion that can be drawn regarding to Martin’s speech acts. In this case, it is related to repetition in his speech acts which is seen as a mean to engage the audience. It is found that that repetition is applied in many of Martin Luther King’s speech acts. In this case, the repetition is applied by Martin to strengthen his thoughts towards racial injustice and discrimination of the Negro people. This is done in order to make sure that the points given by Martin as the sole speaker would be perceived well by the audience since the speech acts deal with such crucial circumstances. Another conclusion can be made regarding to the results and discussion that have been conducted. It is concluded that there are hopes that lies in Martin’s speech acts. Since speech acts are actions via utterance which are intended to make other people to do something, the speech acts are the reflections of Martin’s hopes or desires. They reveal the point of what Martin was striving for during the fight for racial justice. As Martin’s speech acts reveal his intention and hope, it is also seen as a medium used by him to use power. It can be seen that the speech acts show Martin’s influence as the speaker who exposed racial injustices and discrimination of the Negro people. How Martin exercised power is also shown when Martin would like to challenge those who oppose justice for the Negro people. In this case, Martin’s speech acts show that they can affect social change toward the lives of the Negro people. Rather than being aggressive, it is also revealed that Martin’s speech acts are the democratic approach of how Martin exercised power. The speech acts are able to give the audience the urge to fight for justice for the Negro people. SUGGESTION It can be noticed that the study is not written perfectly. The study demands a lot of critiques on many part of it. It is hoped that this research study would be useful to the readers who wanted to use speech acts as the main point of the study. It is suggested that speech acts should be analyzed with knowledge so that it can lead to full understanding. It is also hoped that the study would be a reminder of how important it is to respect people without looking at their racial identity or color skins. Judging people just because of their color skins does not make us any better than anyone else. It is so important to always believe in appreciating other people. REFERENCES Austin, J L. (1962). How to do Things with Words. London: Oxford University Press. Bogdan, R.C.and Bilken, S.K. (1982). Qualitative Research for Education: An Introduction to Theory and Method. Boston: Allyn and Bacon. Brown, G., & Yule, G. (1983). Discourse Analysis. New York: Cambridge University Press. Cruse, A. (2000). Meaning in Language: An Introduction to Semantics and Pragmatics. New York: Oxford University Press. Cutting, J. (2002). Pragmatics and Discourse: A Resource Book for Students. London: Routledge. Fairclough, N. (1989). Language and Power. New York: Longman. Horn, L.R., & Ward, G. (2004). The Handbook of Pragmatics. Malden: Blackwell Publishing. Kulper, K, & Allan, W. S. (1996). An Introduction to English Language: Sound, Word, and Sentence. London: Macmillan Press. Litosetti, L. (2010) Research Methods in Linguistics. London: Continuum. Lofland, D., Snow, D., Anderson, L., & Lofland, L. H. (2006). Analyzing Social Settings: A Guide to Qualitative Observation and Analysis (4th Ed). Belmont: Wadsworth Thomson. Mey, J. L. (1993). Pragmatics: An Introduction. Oxford: Blackwell Publishers. Miles, M, & Huberman, A. (1992). Qualitative Data Analysis: A Source Book of New Methods. London: Sage Publication Mills, S. (2003) Michael Foucault. New York: Routledge. Murmaniati, S. W. (2006) Critical Discourse Analysis on Indonesian Movement: A Study of Speech Act in Soekarno’s Defence Oration “Indonesia Menggugat”. Surabaya: Unesa University Press. Schiffrin, D. (1994). Approaches to Discourse. Cambridge: Blackwell Publishers. Schiffrin, D., Tannen, D., & Hamilton, H.E. (2001). The Handbook of Discourse Analysis. Malden: Blackwell Publishers. Searle, J. R. (1975). A Taxonomy of Illocutionary Acts. Minneapolis: University of Minneapolis Press Searle, J. R. (1979). Expression and Meaning. New York: Cambridge University Press. Searle, J, & Vanderveken, D. (1985). Foundations of Illocutionary Logic. Cambridge: Cambridge University Press. Sidhu, R. K. (2003). Selling Futures: Globalisation and International Education. Queensland: The University of Queensland Press. Stremel, K. (2008). Communication: It Takes Two. 4. Tannen, D. (2007). Talking Voices: Repetition, Dialogue, and Imagery in Conversational Discourse. Cambridge: Cambridge University Press. Weiss, G. & Wodak, R. (2003). Critical Discourse Analysis: Theory and Interdisciplinarity. Hampshire: Palgrave Macmillan. Westbrook, L. (1994). Qualitative Research Methods: A Review of Major Stages, Data Analysis Techniques, and Quality Controls. Michigan: Undergraduate Library, University of Michigan. Yule, G. (1996). Pragmatics. Oxford: Oxford University Press. Yule, G. (2006). The Study of Language (3rd Ed). Cambridge: Cambridge University Press.